Examining Ethical Decisions of Tax Consultants with Javanese Culture: Choosing Ethical Moral Considerations or Conventional Advantages - Yanto, Alif Faruqi Febri; Mustofa, Muhammad Ifan Ali; Ramadhani, Nisha Alia; Rahmawati, Apriana (E-Jurnal Akuntansi, 2024)
This research aims to determine the influence of love of money, emotional intelligence and Machiavellian attitudes on the ethical decisions of tax consultants and is moderated by Javanese culture. The research location that will be studied is the Indonesian Tax Consultant in Malang and Surabaya city. The population of tax consultants was recorded as 146 tax consultants and a sample of 100 tax consultants was taken. Then testing will be carried out using moderated analysis smart PLS 3.0. The research results show that love of money and machiavellianism have a significant effect on tax consultants' ethical decision making, emotional intelligence has no effect on tax consultants' ethical decision making. Javanese culture moderates the relationship between love of money and machiavellianism, and emotional intelligence cannot be moderated by Javanese culture on the ethical decision making of tax consultants.